Daily Protein Intake among Stunted Toddlers in Cimahi, Indonesia - Nurhayati, Ai Nurhayati; Yustiani, Anggi; Patriasih, Rita; Mahmudatusaadah, Ai (The Food and Nutrition Society of Indonesia in collaboration with the Department of Community Nutrition, IPB University, 2023)
This study aimed to determine daily protein intake levels in stunted toddlers. This study involved 64 mothers of stunted toddlers aged 1‒5 years. Daily protein intake was assessed using the semi-quantitative Food Frequency Questionnaire (FFQ). The results show that children aged 1‒3 years had a moderate category of protein intake of 18.9±8.4 g. Meanwhile, children aged 4‒5 years had a less good category of protein intake of 20.0±6.3 g.